Brain Boosting: brain training puzzles & facts to keep your brain young - "Powell, Michael" (Bath, 2014)
This practical book is packed with brain-boostng ideas and challenges. With lots of fun and testing exercises, puzzles and quizzes, Brain Boosting will sharpen your wits, hone your mental skills, transform your concentration and improve your memory. Keep your brain youthful and fit and improve well-being.
Keywords: Puzzles